(untitled) (Journal of the Management Sciences, 2024)
Poor quality of institutions is detrimental to the performance of health sector. This study investigated the nexus between institutional quality and health outcomes in Nigeria. Time series secondary data were sourced form world development indicators and world governance indicators from 1988 to 2022. The study employed the Auto-regressive Distributed Lag Model. The short run result revealed that government effectiveness and political stability both have a negative and significant impact on maternal mortality rate in Nigeria while control of corruption on the other hand has a significant positive impact on life expectancy. The long-run result revealed that all the institutional quality indicators except control of corruption are positive and significant on both health outcomes. Based on the findings, the study recommended that efforts should be made to enhance control of corruption, strengthening the rule of law, promoting political stability, combating violence and terrorism, and improving government effectiveness. These policy measures can positively impact maternal health outcomes and overall life expectancy by ensuring transparent and accountable healthcare systems, equal access to justice, peaceful environments, and effective governance of healthcare resources.